Child growth faltering dynamics in food insecure districts in rural Ethiopia - Hirvonen, Kalle; Wolle, Abdulazize; Laillou, Arnaud; Vinci, Vincenzo; Chitekwe, Stanley; Baye, Kaleab (Wiley, 2024)
Child undernutrition disproportionally affects children in low- and middle-income countries. In Ethiopia, both wasting and stunting are serious public health concerns, with high human and economic costs. Understanding the dynamics in ponderal and linear growth faltering is critical to inform the design of innovative interventions that can prevent both wasting and stunting in poor and complex settings. Using two longitudinal studies conducted in 2017 and 2019 in four highland regions of Ethiopia, we evaluated the dynamics and drivers of child growth faltering in children 6–23 months of age (N = 5003). Child wasting prevalence peaked during the first 6 months of life, whereas stunting increased significantly after 6 months of age. Male sex, child illnesses (i.e., diarrhoea or fever) and low consumption of fruits and vegetables were associated with higher odds of acute undernutrition (P < 0.05). The consumption of animal source foods (ASF) was associated with increases (β: 95% CI) in weight-for-length Z-score (WLZ; 0.12: 0.0002; 0.242), whereas fruit or vegetables consumption was associated with increases in midupper arm circumference (MUAC; 0.11 cm: 0.003; 0.209). Only consumption of ASF was the statistically significant predictor of future linear growth (0.14: 0.029; 0.251). Distinct trends in WLZ and MUAC were observed by child sex and age. Improving diet quality through improved nutrition knowledge and increased access and affordability of ASFs, along with effective infection prevention/control measures could prevent both child wasting and stunting concurrently.